The influence of the Drygalski Ice Tongue on the local ocean - Stevens, Craig; Sang Lee, Won; FUSCO, Giannetta; Yun, Sukyoung; Grant, Brett; Robinson, Natalie; Yeon Hwang, Chung (Annals of Glaciology, 2017)
The Drygalski Ice Tongue presents an âˆ1⁄480 km long floating obstacle to alongshore flows in the Victoria Land coastal ocean region of the Western Ross Sea. Here we use oceanographic data from near to the tongue to explore the interplay between the floating glacier and the local currents and stratification. A vessel-based circuit of the glacier, recording ocean temperature and salinity profiles, reveals the southwest corner to be the coldest and most complex in terms of vertical structure. The southwest corner structure beneath the surface warm, salty layer sustains a block of very cold water extending to 200 m depth. In this same location there was a distinct layer at 370 m not seen anywhere else of water at âˆ1⁄4âˆ’1.93Â°C. The new observations broadly, but not directly, support the presence of a coherent Victoria Land Coastal Current. The data suggest the northward moving coastal current turns against the Coriolis force and works its way anticlockwise around the glacier, but with leakage beneath the glacier through the highly â€˜rippledâ€™ underside, resulting in a spatially heterogeneous supply to the Terra Nova Bay Polynya region â€“ an important location for the formation of high-salinity shelf water.